STRUCTURE OF THE BENTHIC EPIFAUNA COMMUNITY IN MANGROVE ECOTOURISM AREA IN PANGKALAN JAMBI VILLAGE, BUKIT BATU DISTRICT, BENGKALIS REGENCY - Arniati, Dina; Efriyeldi, Efriyeldi; Mubarak, Mubarak (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2021)
Benthic epifauna are animals that generally live in coastal waters such as sandy/muddy beaches, coral reef ecosystems and mangrove ecosystems. The purpose of this study was to analyze the structure of the benthic epifauna community in Mangrove ecotourism, Pangkalan Jambi Village, Bukit Batu District, Bengkalis Regency. This study uses a survey method. Epifauna community structure parameters taken include species, abundance, diversity, uniformity, and dominance. The environmental parameters measured included water quality, substrate type and total organic matter content of the sediment. The number of species found was 9 species from 2 classes, namely Gastropods and Malacostraca with the most dominant species found, namely the benthic epifauna species Cerithidea quadrata. The highest abundance of benthic epifauna species Cerithidia quadrata was 1.04 Ind/m2. Based on the ANOVA test with a significant value of 0.115> 0.05, it means that the preference of the betik epifauna between stations was not significantly different.